Discovering Intellectual Capital through Photos - Intan Pratiwi; Ani Wilujeng Suryani (Atestasi : Jurnal Ilmiah Akuntansi, 2021)
Intellectual Capital (IC) is an intangible asset that is important for a company to increase value. However, only a few reports IC because IC reporting is not mandatory, although this information is essential for stakeholders' decision making. This study aims to investigate the disclosure of IC through photos in annual reports and to analyze the purpose of using these photos. This research is different from prior studies by using data in the form of images depicting IC in annual reports. This mixed methods research used a visual content analysis approach within a frame of impression management theory to analyze the intent of using photos, followed by a statistical differential test. This study used 2360 photos contained in 38 annual reports of service companies. This study found a narcissistic leader tendency and the existence of the glass ceiling phenomenon. In addition, human capital was the most frequently disclosed IC component. The impression management carried out by the company was also found through the specific and non-specific photos displayed. This research is expected to be used as a reference for the development of future accounting research. In addition, this research is also expected to provide an understanding of the use of photos in representing reality in annual reports so that it could be helpful in stakeholders' decision-making,